Stability of nivolumab in its original vials after opening and handing in normal saline bag for intravenous infusion. (August 2020) - Le Guyader, G.; Vieillard, V.; Mouraud, S.; Do, B.; Marabelle, A.; Paul, M.
Abstract: Objectives: Nivolumab is an anti–programmed cell death-1 monoclonal antibody, approved for numerous indications in oncohaematological cancers. It is available as solution for infusion at 10 mg/ml. In accordance with the Summary of Product Characteristics (SmPCs), the product is stable for 24 h at 2–8 °C after dilution. However, to anticipate the needs and constraints related to the handling of the product, the aim was to obtain additional information that will contribute to the risk assessment in case of deviation. Potential changes in the stability of Opdivo® leftovers (10 mg/ml) and diluted nivolumab in normal saline solution (2 mg/ml) over a period exceeding 24 h, at different temperatures and after freezing/thawing cycles were studied. Methods: Turbidimetry, Ultraviolet (UV)-spectroscopy, dynamic light scattering and chromatography were used to evaluate physicochemical stability. Potential pharmacological variations were monitored in vitro by a functional binding inhibition method. Results: No change was detected after 1 month of storage at 2–8 °C neither after 7 days at 40 °C. Although slight changes were detected only after 3 months under 2–8 °C, major changes were found for the same period of time at 40 °C (variants in the distribution profile, slight increase in oligomers and fragments and UV spectral modifications). Physical instability was observed upon 3 freeze/thaw cycles, with the appearance of a new protein population associated with an increase in polydispersity index. Conclusion: In conclusion, our results provide additional rationale to the SmPCs, regarding the use of leftovers, reassignment of bags, pre-preparation or breaking the cold chain for Nivolumab. Graphical abstract: Image 1 Highlights: It is the first physical and functional stability study of concentrated and diluted nivolumab using validated and orthogonal advanced methods. This work validates the use of nivolumab after a temperature excursion. Nivolumab is stable 1 month at 2–8 °C and 7 days at 40 °C. This work could dramatically reduce the cost of immunotherapy trials and contribute to the improvement of scientific knowledge.